Personalized Inclusion with GenAI: An Adaptive Strategy to Support Students with ASD in Higher Education - Otemaier, Rafaela; Quevedo, Eros; Valaski, Joselaine; Tomaschitz, Joice de O. P.; Malucelli, Andreia (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2025: Anais do XXXVI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2025.12168, 2025)
Inclusion in abstract, cognitively demanding courses is difficult. This study presents an adaptive strategy that merges Universal Design for Learning (UDL) and Generative AI to tailor propositional-logic activities for a student with Autism Spectrum Disorder (ASD). Across four formative, reflective cycles, existing tasks were progressively reshaped; evidence came from observations, journals, and rubrics. The ASD learner showed sustained gains in engagement, conceptual grasp, and autonomy, indicating the value of the approach. The results suggest that educator-mediated GenAI, aligned with UDL, can foster more responsive and inclusive learning in higher education.